2024
DOI: 10.1002/jsfa.13434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salting and dehydration treatments on the physicochemical and gel properties of hen and duck egg yolks, plasma and granules

Yujie Su,
Yuanyuan Sun,
Cuihua Chang
et al.

Abstract: BackgroundSalted hen egg yolks are less oily and less flavorful than salted duck egg yolks. However, hen eggs have a more adequate market supply and have a broader application prospect than duck eggs. In this study, egg yolks, plasma, and granules were dehydrated by adding 1% NaCl to simulate traditional curing process of salted egg yolk. The changes in the pickling process of hen egg yolks (HEY) and duck egg yolks (DEY) plasma, and granules were compared to reveal the gelation mechanism and the underlying cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Juhaimi et al [6] observed that various cooking methods significantly impact the oil content. According to previous reports, most of the lipids in egg yolk are present in low-density lipoproteins (LDLs) [23]. During saltinduced processing, free lipids may be released from LDL micelles due to changes in LDL structure caused by dehydration and high salt conditions.…”
Section: Oil Exudationmentioning
confidence: 99%
“…Juhaimi et al [6] observed that various cooking methods significantly impact the oil content. According to previous reports, most of the lipids in egg yolk are present in low-density lipoproteins (LDLs) [23]. During saltinduced processing, free lipids may be released from LDL micelles due to changes in LDL structure caused by dehydration and high salt conditions.…”
Section: Oil Exudationmentioning
confidence: 99%